Visceral protein pool in highly skilled kayakers and canoeists - Makarova, G.A.; Pogrebnoy, A.I.; Chernuha, S.M.; Karpov, A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the adequacy of delayed post-exercise recovery of total protein and albumin content in venous blood as criteria for visceral protein pool in highly skilled kayakers and canoeists. Methods and structure of the study. Summary of data from literary sources substantiating the particular importance of athletes consuming the necessary amount of protein. Monitoring of haematocrit, total protein, albumin and haemoglobin concentration in venous blood in highly skilled kayakers and canoeists. 79 male athletes aged 18 to 37 were examined (20 honoured masters of sport, 23 international class masters of sport of Russia, 36 masters of sport; 40 people were examined repeatedly). Venous blood was collected in the morning, 40 hours after the end of the last training session. Blood analysis was performed at the Regional Clinical Hospital No. 1 named after Professor S. V. Ochapovsky (Krasnodar). Results and conclusions. All analysed indicators show significant differences at haematocrit values above and below 47%, which corresponds to the 75th centile of this parameter. The interval of mean values of total protein content in the range ±1 σ is 69.62±3.86 g/l, i.e. its upper values (73.48 g/l) are significantly lower than the upper values of the reference interval recommended for clinical practice (68-85 g/l). In 38.8% of measurements, the total protein content in athletes was below 69.62 g/l, of which 29.3% were below 65.76 g/l. In addition, four rowers had total protein levels below 69.62 g/l for two years, and two had levels below 65.76 g/l. A certain correlation between total blood protein and haemoglobin concentration was also established. The results obtained allow us to conclude that highly skilled kayakers and canoeists may experience a marked decrease in the visceral protein pool due to globulin fractions during routine monitoring, which may negatively affect the state of the immune system and blood coagulation system, to a certain extent contribute to a decrease in haemoglobin content and, in general, to the effectiveness of the training process.